Customer service management strategies for loyalty: A systematic review - Charles Augusto Ortiz Briceño; Luis Miguel Romero Echevarria; Martin William Huisa Huahuasoncco; Nataly Silvia Garcia Vilca; Denilson Medina Sanchez (International Journal of Medical Toxicology and Legal Medicine, 2024)
In recent years, customer service management has had to implement strategies that go beyond providing products and services to provide an experience that achieves customer loyalty. This research focused on carrying out a literature review following the PRISMA methodology, for which relevant documentation referring to the topic of study was retrieved. From a total of 31 indexed publications, 19 articles obtained from SciELO and Scopus were analysed. At the end of the corresponding research, it was concluded that customer service management strategies are related to customer loyalty, which is why their correct implementation helps to create lasting and beneficial relationships between the company and the consumer.